2016
DOI: 10.1002/2016gl069896
|View full text |Cite
|
Sign up to set email alerts
|

Modification of land‐atmosphere interactions by CO2 effects: Implications for summer dryness and heat wave amplitude

Abstract: Plant stomata couple the energy, water, and carbon cycles. We use the framework of Regional Climate Modeling to simulate the 2003 European heat wave and assess how higher levels of surface CO2 may affect such an extreme event through land‐atmosphere interactions. Increased CO2 modifies the seasonality of the water cycle through stomatal regulation and increased leaf area. As a result, the water saved during the growing season through higher water use efficiency mitigates summer dryness and the heat wave impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Deep soil layers do not dry as much as surface soil layers, and in some places even show the opposite sign to the soil above [41]. This is consistent with the idea that plants are using less water under higher CO 2 concentrations, and that water may be stored at depth in the soil [12,42].…”
Section: What Are Appropriate Drought Metrics For the Future?supporting
confidence: 74%
“…Deep soil layers do not dry as much as surface soil layers, and in some places even show the opposite sign to the soil above [41]. This is consistent with the idea that plants are using less water under higher CO 2 concentrations, and that water may be stored at depth in the soil [12,42].…”
Section: What Are Appropriate Drought Metrics For the Future?supporting
confidence: 74%
“…These two mechanisms, in turn, affect seasonal soil moisture depletion that can further enhance future heat waves or droughts (Lemordant et al, 2016). However, global averages hide substantial variability across regions.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2003 centennial European drought, Leuzinger et al (Leuzinger & Körner, 2007) recorded higher transpiration rates for some species and locally reduced temperature in the experimental higher [CO 2 ] area. A model study (Lemordant et al, 2016) showed that stomatal response to higher [CO 2 ] can generate soil water savings during the growing season ( Figure 1c) and enhanced water availability during the summer, feeding larger transpiration during a summer heat wave and thereby mitigating its severity (Figure 1c). …”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, observational studies to date show that ecosystem‐specific properties can significantly influence the dynamics of land evaporation during droughts and heatwaves. Since these differences lead in turn to contrasting surface partitioning of radiation, it is safe to argue that land conditions and plant physiology at ecosystem scales have the potential to influence the state and evolution of the atmospheric boundary layer during these extreme events, and thus impact the development of extreme meteorological conditions . Along these lines, it is crucial to acknowledge the extent to which Figure simplifies key processes, and to highlight that any change on the atmospheric boundary layer that is triggered by the surface partitioning of radiation, will affect the stability and growth of the boundary layer, and therefore (1) the entrainment of air from the top and (2) the potential influence of air advection from the surrounding.…”
Section: Lessons Learned From Observationsmentioning
confidence: 99%
“…Regional climate simulations—in which the boundary conditions are typically prescribed based on reanalysis data of temperature, humidity, and wind profiles—are frequently used to investigate single events . The influence of land conditions on the particular extreme event can be isolated as long as the domain of interest is sufficiently large so that humidity and temperature in the region are not fully determined by the reanalysis data on the boundaries …”
Section: Findings From Coupled Climate Modelsmentioning
confidence: 99%